The Effect of Tax Rate Reduction in the Income Tax Act 2008 on Policy for Preparation of Financial Statements ( A Study on the Future of Public Manufacturing Companies in the Era of Tax Reform) - Christine Christine; Yulianti Yulianti (The Indonesian Journal of Accounting Research, 2013)
As corporate income tax is considered an important tax for developing countries, the governments in these countries has continuously tried to modify corporate income tax structure in order to optimize their tax revenues. This study aims to examine the responsiveness of corporate taxable income to tax structure changes in Indonesia by analyzing Indonesian the corporate tax rate reduction in 2008. This study investigates how corporate taxpayers respond to the tax rate changes, whether and to what extent corporate taxpayers alter their behavior in ways that affect their taxable income. Using a current accrual model as used by Guenther (1994), this study shows that future reduction in tax rate has negative effect on current earnings, which means firms tried to shift their income from the current period to future periods to obtain tax benefits. Further, this research also finds that foreign ownership and existing loss compensation affect the probabilities of companies conducting earnings management. Based on these results, policy makers in Indonesia should take into consideration the behavioral effect of changes in income tax legislation and integrate this effect into their future policy development.